Effect of P doped bimetallic FeCo catalysts on carbon matrix for oxygen reduction in alkaline media - Yuqi Ma; Hyo-Jin Ahn (Science and Technology of Advanced Materials)
Catalysts’ redox reactions are crucial for storage and energy conversion. Therefore, the fabrication of cost-effective, structurally rational, and multifunctional advanced catalytic materials continues to be a crucial task. In this study, we obtained P, Fe, and Co co-doped, nitrogen-rich carbon nanofibers by directly forming carbon nanotubes from metal-organic frameworks through electrospinning and pyrolysis. The P0.025-FeCo/C catalyst demonstrated outstanding ORR activity, including an ECSA of 1954.3 cm2, a limited current density of -3.98 mA/cm2, an E1/2 of ~0.84 V, and an Eonset of ~0.94 V. After 5000 cycles, the P0.025-FeCo/C catalyst demonstrated remarkable enduring stability. These function enhancements occurred because of the electronic coupling between the metal and phosphorus, which altered the electron distribution at the metal center and optimized its electronic structure, thereby improving catalytic activity and stability. It exhibits good chemical stability in alkaline media and can maintain its catalytic performance for a long time, demonstrating good durability. Its tubular structure provides many active sites and superior electron transport paths owing to its unique channels and cavities, which help improve its activity and stability. Therefore, P0.025-FeCo/C is expected to become a non-precious metal catalyst for facilitating oxygen reduction reactions.